ANALYSIS OF PROPOSED IMPROVEMENTS TO MINIMIZE PIPE LEAKS AND DECREASE IN WATER QUALITY USING TOTAL QUALITY MANAGEMENT METHOD: A CASE STUDY OF PT.XYZ - Gadih Ranti; Ni Made Sudri; Yenny Widianty; Ade Haris Sutisna (Center for Study and Journal Management FTI UMI, 2022)
PT. XYZ is a company engaged in the management of clean water supply systems in an ABC industrial area managed by PT. ABC. PT.XYZ experienced the problem of water loss which can be categorized as high in the production process of 15.5% and in the distribution process of 32.6%, where this value exceeds the standard set by the government. This water loss is caused by pipe leaks, which then has an impact on the declining quality of clean water. In this study, the TQM (Total Quality Management) approach was used to overcome these problems. Based on research, the company has implemented the majority of the principles of TQM and has a positive impact on better performance in providing clean water for PT.ABC. The recommendation is proposed by investing in additional infrastructure in the form of a Water Treatment Plant (WTP).